Evaluation of standardized questionnaire to assess health literacy in children and teenagers ant the utilization in practice - Machová, Alena; null, null; Boledovičová, Mária; Nováková, Dita (STEF92 Technology Ltd., 2017)
The goal of this paper is to present the research project ZGO2016_001 called "Health Literacy in Selected Group of the South Bohemian Population" and to inform about results of health literacy in children and adolescents group.
Vyhodnocení standardizovaného dotazníku pro hodnocení zdravotní gramotnosti u dětí a mládeže a využití v praxi
Keywords: Evaluation; health; literacy; children and teenagers; Vyhodnocení; zdravotní gramotnosti; dětí a adolescenti